Ação de sais minerais solúveis em alvenaria de tijolos cerâmicos no município de Petrolina-PE - Ribeiro, Ariosvaldo Gomes (2013)
The work discusses about the effects of soluble salts action on ceramic brick masonry walls in Petrolina-PE. To understand this phenomenon a mapping of pathologies on walls related with soluble salt action was performed and monitoring wells were installed to capture groundwater in five places on the city where the phenomenon occurs more frequently. Samples of soils and groundwater as well as samples of ceramic bricks and level of chloride in the atmosphere were collected and analyzed in laboratory to assess their properties. Obtained results showed pathological manifestations observed on ceramic bricks walls in building localized on the areas studied are strongly influenced by the high content of soluble salts found in samples of soils and groundwater in the city and not by the content of chloride in the atmosphere.